Get live Maths 1-on-1 Classs - Class 6 to 12

Miscellaneous

Misc 1

Misc. 2 Important Deleted for CBSE Board 2023 Exams

Misc 3

Misc 4

Misc 5

Misc 6 Important You are here

Misc 7 Important

Misc 8

Misc 9

Misc 10

Misc 11 Important Deleted for CBSE Board 2023 Exams

Misc 12 Important Deleted for CBSE Board 2023 Exams

Misc. 13 Deleted for CBSE Board 2023 Exams

Misc 14 Deleted for CBSE Board 2023 Exams

Misc. 15 Important Deleted for CBSE Board 2023 Exams

Misc. 16 Important

Misc 17 (MCQ) Important Deleted for CBSE Board 2023 Exams

Misc 18 (MCQ)

Misc 19 (MCQ) Important

Matrices and Determinants - Formula Sheet and Summary Important

Chapter 4 Class 12 Determinants

Serial order wise

Last updated at March 16, 2023 by Teachoo

Misc 6 Prove that |■8(a2&bc&[email protected]+ab&b2&[email protected]&b2+bc&c2)| = 4a2b2c2 Solving L.H.S |■8(a2&bc&[email protected]+ab&b2&[email protected]&b2+bc&c2)| = |■8(𝐚(𝑎)&𝐛(c)&𝐜(a+c)@𝐚(𝑎+𝑏)&𝐛(b)&𝐜(a)@𝐚(𝑏)&𝐛(b+c)&𝐜(c))| Taking out a common from C1 ,b common from C2 & c common from C3 = abc |■8(a&c&[email protected]𝑎+𝑏&b&[email protected]𝑏&b+c&c)| Applying C1→ C1 + C2 + C3 = abc |■8(a+𝑐+𝑎+𝑐&c&[email protected]𝑎+𝑏+𝑏+𝑎&b&[email protected]𝑏+𝑏+𝑐+𝑐&b+c&c)| = abc |■8(2a+2𝑐&c&[email protected]+2𝑏&b&[email protected]𝑏+2𝑐&b+c&c)| = abc |■8(𝟐(𝑎+𝑐)&c&[email protected]𝟐(𝑎+𝑏)&b&[email protected]𝟐(𝑏+𝑐)&b+c&c)| Taking out 2 Common from C2 = 2a𝑏𝑐|■8((𝑎+𝑐)&c&[email protected](𝑎+𝑏)&b&[email protected](𝑏+𝑐)&b+c&c)| Applying C3→ C3 – C1 = 2a𝑏𝑐|■8((𝑎+𝑐)&c&a+c−(𝐚+𝐜)@(𝑎+𝑏)&b&a−(a+b)@(𝑏+𝑐)&b+c&c−(b+c))| = 2a𝑏𝑐|■8(𝑎+𝑐&c&𝟎@𝑎+𝑏&b&−𝑏@𝑏+𝑐&b+c&−b)| Applying C2→ C2 – C1 = 2abc |■8(𝑎+𝑐&c−(𝑎+𝑐)&[email protected]𝑎+𝑏&b−(𝑎+𝑏)&−[email protected]𝑏+𝑐&b+c−(𝑏+𝑐)&−b)| = 2abc |■8(𝑎+𝑐&−𝒂&[email protected]𝑎+𝑏&−𝒂&−𝐛@𝑏+𝑐&0&−𝐛)| Taking out –a common from C2, –b common from C3 = 2abc (–a) (–b) |■8(𝑎+𝑐&1&[email protected]𝑎+𝑏&1&[email protected]𝑏+𝑐&0&1)| Expanding Determinant along R1 = 2a2b2c ((a+c)|■8(1&[email protected]&1)|−1|■8(𝑎+𝑏&[email protected]𝑏+𝑐&1)|+0|■8(𝑎+𝑏&[email protected]𝑏+𝑐&0)|) = 2a2b2c ((a+c)|■8(1&[email protected]&1)|−1|■8(𝑎+𝑏&[email protected]𝑏+𝑐&1)|+0) = 2a2b2c ((a + c) (1 – 0) – 1(a + b – (b + c))) = 2a2b2c ((a + c) (1) – 1 (a + b – b – c)) = 2a2b2c (a + c – a + c) = 2a2b2c (2c) = 4a2b2c = R.H.S Hence proved